3D orthogonal multi-resolution analysis of flow structures around an improved vehicle external mirror. (May 2021) - Dong, Lin; Rinoshika, Akira
This paper proposes vehicle door mirrors with a tip shape and ditch to reduce the aerodynamic drag. The mean drag coefficients Cd of various mirror models were first measured using load cells within a 10 3 –10 5 Reynolds number range in a wind tunnel. The Cd of controlled mirrors with different ditch widths remained constant at approximately 0.75 and was lower than that of conventional mirrors. Using a large eddy simulation (LES), the 3D flow structures around modified and conventional mirrors were numerically analyzed at a Reynolds number of 2.8 × 10 5 . Based on a three-dimensional orthogonal wavelet multi-resolution technique, the instantaneous three-dimensional vorticity and velocity were decomposed into three wavelet levels or scales: large scale with a 62 mm central scale, intermediate scale with a 29 mm central scale, and small scale with a 16 mm central scale. This indicated that the length of the region of the vorticity iso-surfaces in an improved door mirror model as the tip ditch decreases. Because the tip ditch produced the more streamwise vortices, the large-scale spanwise vortices were suppressed. The streamwise vortices and spanwise vortices of the small- and intermediate-scale structures increased, which is mainly caused by the ditch in the tip.